Building an Effective Cybersecurity Program, 2nd Edition : a Security Manager's Handbook - Schreider, Tari (Rothstein Associates, Incorporated, 2019)
You are either part of the digital economy or reliant upon it. With critical information assets at risk, each company requires a state-of-the-art cybersecurity program. But how can companies achieve the best possible program? This book explores the process of developing an effective cybersecurity system.